The creative reflective practitioner : research through making and practice - Candy, Linda (Routledge, 2020)
The Creative Reflective Practitioner explores research and practice through the eyes of people with a wholehearted commitment to creative work. It reveals what it means to be a reflective creative practitioner, whether working alone, in collaboration with others, with digital technology or doing research, and what we can learn from listening and observing closely. It gives the reader new insights into the fascinating challenge that having a reflective creative mindset can bring. Creative reflective practice is seen through practitioner ideas and works which have informed the writing at every level, supported by research studies and historical accounts. The practitioners featured in this book represent a broad spectrum of interdisciplinary creative activities producing works in film, music, drama, dance and interactive installations. Their work is innovative, full of new ideas and exciting to experience, offering engagement and challenge for audiences and participants alike. Practitioner interviews give a direct sense of how they see creative practice from the inside. The ways in which these different situations of practice stimulate and facilitate reflection in practice and how we can learn from this are described. Variations of reflective practice are discussed that extend the original concepts proposed by Donald Schön, and a contemporary dimension is added through the role of the digital in creative reflective practice as a tool, mediator, medium and partner. This book is relevant to people who wish to understand creativity and reflection in practice and how to learn from the practitioners themselves. This includes researchers in any discipline as well as students, arts professionals and practitioners such as artists, curators, designers, musicians, performers, producers and technologists.